Baicalein Protects against Type 2 Diabetes via Promoting Islet β-Cell Function in Obese Diabetic Mice. (23rd July 2014) - Fu, Yu; Luo, Jing; Jia, Zhenquan; Zhen, Wei; Zhou, Kequan; Gilbert, Elizabeth; Liu, Dongmin
Abstract : In both type 1 (T1D) and type 2 diabetes (T2D), the deterioration of glycemic control over time is primarily caused by an inadequate mass and progressive dysfunction of β -cell, leading to the impaired insulin secretion. Here, we show that dietary supplementation of baicalein, a flavone isolated from the roots of Chinese herb Scutellaria baicalensis, improved glucose tolerance and enhanced glucose-stimulated insulin secretion (GSIS) in high-fat diet (HFD-) induced middle-aged obese mice. Baicalein had no effect on food intake, body weight gain, circulating lipid profile, and insulin sensitivity in obese mice. Using another mouse model of type 2 diabetes generated by high-fat diet (HFD) feeding and low doses of streptozotocin injection, we found that baicalein treatment significantly improved hyperglycemia, glucose tolerance, and blood insulin levels in these middle-aged obese diabetic mice, which are associated with the improved islet β -cell survival and mass. In the in vitro studies, baicalein significantly augmented GSIS and promoted viability of insulin-secreting cells and human islets cultured either in the basal medium or under chronic hyperlipidemic condition. These results demonstrate that baicalein may be a naturally occurring antidiabetic agent by directly modulating pancreatic β -cell function.